Birch Reduction and Its Application in the Total Synthesis of Natural Products - Zhang, Guoqiang; Shen, Yaojia; Wang, Miao; Guo, Yunqi; Wang, Hengyi (International Journal of Materials Science and Technology Studies, 2025)
The Birch reduction, a classical organic transformation discovered by Arthur J. Birch in 1944, remains a powerful and indispensable tool for the partial reduction of aromatic compounds. This review delves into the mechanistic underpinnings of the reaction, emphasizing its predictable regioselectivity governed by substituent effects. Its principal focus is on showcasing the strategic application of the Birch reduction as a key step in the total synthesis of complex natural products. Several case studies are examined, including syntheses of steroids, terpenoids, and alkaloids, highlighting how Birch-derived intermediates enable the efficient construction of intricate molecular architectures. Furthermore, the integration of this classic method with modern organometallic and pericyclic reactions is discussed, underscoring its enduring relevance and evolving potential in synthetic organic chemistry. This review systematically examines the mechanistic principles underlying this transformation, with particular emphasis on its well-defined regioselectivity—a predictable outcome governed by the electronic nature of aromatic substituents through resonance and inductive effects. The central focus of this discussion lies in elucidating the strategic implementation of Birch reduction as a pivotal disconnection in the total synthesis of structurally complex natural products. Through representative case studies encompassing steroids, terpenoids, and alkaloids, we demonstrate how Birch-derived diene and enol ether intermediates serve as key building blocks for the efficient and stereo controlled assembly of intricate molecular architectures. Furthermore, this analysis explores the productive integration of this classical protocol with contemporary synthetic strategies, including transition metal-mediated transformations and concerted pericyclic processes, thereby highlighting its enduring relevance and continuing evolution as a fundamental tool in modern synthetic organic chemistry.